OVARIAN CYST HYDATID. CASE REPORT - Urbina Álvarez, Claudia (2015)
We report a case of ovarian hydatic cyst, of rare presentation, without evidence of systemic hydatidosis in a 29 year-old woman with one previous delivery and an abortion, admitted to the Gynecology Service with the diagnosis of right adnexal tumor. A unilocular cyst was removed by laparotomy and the diagnosis was ovarian hydatidic cyst by pathological examination. We describe the clinical, ultrasound and histologic characteristics.